Stimuli-responsive In situ gelling system for nose-to-brain drug delivery - Agrawal, Mukta; Saraf, Shailendra; Saraf, Swarnlata; Dubey, Sunil K.; Puri, Anu; Gupta, Umesh; Kesharwani, Prashant; Ravichandiran, V.; Kumar, Pramod; Naidu, V.G.M.; Murty, Upadhyayula Suryanarayana; Ajazuddin; et al. (Journal of controlled release, 2020)
The diagnosis and treatment of neurological ailments always remain an utmost challenge for research fraternity due to the presence of BBB. The intranasal route appeared as an attractive and alternative route for brain targeting of therapeutics without the intrusion of BBB and GI exposure. This route directly and effectively delivers the therapeutics to different regions of the brain via olfactory and trigeminal nerve pathways. However, shorter drug retention time and mucociliary clearance curtail the efficiency of the intranasal route. The in situ mucoadhesive gel overthrow the limitations of direct nose-to-brain delivery by not only enhancing nasal residence time but also minimizing the mucociliary clearance and enzymatic degradation. This delivery system further improves the nasal absorption as well as bioavailability of drugs in the brain. The in situ mucoadhesive gel is a controlled and sustained release system that facilitates the absorption of various proteins, peptides and other larger lipophilic and hydrophilic moieties. Owing to multiple benefits, in situ gelling system has been widely explored to target the brain via nasal route. However, very few review works are reported which explains the application of in situ nasal gel for brain delivery of CNS acting moieties. Hence, in this piece of work, we have initially discussed the global statistics of neurological disorders reported by WHO and other reputed organizations, nasal anatomy, mechanism and challenges of nose-to-brain drug delivery. The work mainly focused on the use of different stimuli-responsive polymers, specifically thermoresponsive, pH-responsive, and ion triggered systems for the development of an effective and controlled dosage form, i.e., in situ nasal gel for brain targeting of bioactives. We have also highlighted the origin, structure, nature and phase transition behavior of the smart polymers found suitable for nasal administration, including poloxamer, chitosan, EHEC, xyloglucan, Carbopol, gellan gum and DGG along with their application in the treatment of neurological disorders. The article is aimed to gather all the information of the past 10 years related to the development and application of stimuli-responsive in situ nasal gel for brain drug delivery. [Display omitted] •Sol-gel transformation of biomaterials upon exposure to physiological stimulus.•Stimuli responsive in situ nasal gel increases drug retention and lessen mucociliary clearance.•Increases bioavailability of drug in brain through olfactory and trigeminal nerve passage.•Removes the barriers of direct nose-to-brain drug delivery.•Suitable for large lipophilic moieties like proteins, peptides and also small hydrophilic substances.